Bias Gender Dalam Kartun Editorial Di Media Cetak - Basnendar Herry Prilosadoso (Institut Seni Indonesia Surakarta, 2007)
People as human being separated in two which are male and female, the difference called gender. Those differentiation base from biological function especially reproduction. Derivation from the natural aspect of male and female is bearing the gender concept that was effect from social construction. Once form of social construction that has relation with the differentiation gender peeping out gender term.Study cartoon and caricature means to look out on visual sign and word. This study use critical study with aims to unfold the meaning of sign or symbol. Unfolding that things isnâ€™t easy because there are a lot of problem expanding in society especially social and politic problem. Other, the cartoon and caricature element are complex. Itâ€™s consists from many science, for example fine arts, art, linguistic, etc.Cartoon is a picture that represent symbolic sign, consist insinuate, joke or humour. On publication cartoon attend in periodic time, almost of them focus with political and public problem. Rarely social problem became a target, example the society behaviour, gym or someone personality.Keyword: Gender, Cartoon Editorial, MetaphorÂ